Self-Assessment of Students’ Anxiety during High Stake Laboratory Work Examinations (Journal of Education and Educational Development, 2020)
The present study intends to explore the level of practical examination anxiety among secondary and higher secondary school students and its causes and remedies. A self-developed Perceived Science Practical Anxiety Scale (PSPAS) was used to collect quantitative data from 900 science students of two districts of central Punjab: Sargodha and Faisalabad. Moreover, 50 students were interviewed to explore their perceptions of the causes of science practical examination anxiety and the remedies to reduce it. All students had recently taken science practical examination and therefore had first-hand vivid experience of science practical examination anxiety. The analysis of responses in the questionnaire revealed that on an average more than half (61.50 %) of the students experienced anxiety during practical examination. Fourteen sources of anxiety during practical examination were ranked and synthesis of qualitative data from interviews recorded five categories of anxiety causes: shortage and unavailability of the materials, lack of practice, harsh behaviour of laboratory personnel, over loaded syllabus and lack of guidance. The students’ opinion regarding reducing anxiety was synthesized into four themes: relaxation during practical examination, individual level preparation, completion of practical syllabus well before time and training of laboratory personnel. The findings of the study may be beneficial for teachers, school mangers and policy makers and those who are responsible for the preparation and execution of examination policies, to reduce anxiety among students.